(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Memory (in the form of history) is something that helps tradition and culture to be carried to the future generation and at the same time, it is dangerous weapon to create irrelevant myths to keep the marginalized as ever and to keep up patriarchy as ever. Memory is a tool of gratitude and vengeance as well. The paper’s motto is to give a deep study on Margaret Atwood´s The Penelopiad which is the revision of Greek myth The Odyssey and voices the dumb characters’ plight in the classic myth. It argues the issues from theoretical to societal approach. It associates the theme of myth and the theory of feminism with the text of Atwood. Myth is infused with memory of human. The novel is a narration of Penelopiad’s memory which is ignored since years. The paper also describes how the so called feminine qualities were created by society and made women to believe that they must be feminine. It addresses the matter that innocence, love and loyalty of women are played on in every aspect of life. It also brings out that how the female worries in myth and the real world are one and the same. Finally the paper brings out that mythification serves as a powerful weapon used to control the voiceless who tries to voice against suppression.